Nitrogen and phosphorus management on pig farms in Northwest Germany – nutrient balances and challenges for better sustainability - D. Otten; H. F. A. Van den Weghe (African Journal of Pig Farming, 2013)
The study analyses the nutrient flow of nitrogen (N) and phosphorus (P) on six intensive pig farms in Northwest Germany over a period of 5 years. The study investigated the farmers’ management of nutrient flows associated with intensive pig farming, focusing especially on the management of manure. It could be shown that in intensive pig production, high performance and performance-related feeding positively affects nutrient flow efficiency. However, on the crop production side of the farms, there existed a great disharmony between the farmers’ perception of manure used as (N, P) fertiliser on their crops and the real quantity of nutrients produced by their intensive pig farming. The farmers were unable to estimate the fertiliser effect of their manure correctly [underestimation N = 7.6% (10.6 kg/ha), P = 33.6% (11.6 kg/ha)]. The application of nutrients by mineral fertiliser was underestimated also [N by 4.1% (8.1 kg/ha), P by 12.7% (1.5 kg/ha)] and were inadequately attuned to the large amount of manure produced by their intensive pig production. As a result, the farms had large nutrient losses (104.5 kg N/ ha; 11.7 kg P/ha) and were unable to fulfil the minimum German legal requirements for fertiliser application. The study evaluated the critical aspects of nutrient management and discusses possible improvements for the future.